The effect of temperature and crystallite size on the growth and morphology of carbon nanotubes - Kleinsmidt, Jacques N (Department of Chemical Engineering, 2014)
The aim of the study was to synthesise iron oxide crystallites with different crystallite sizes supported on y-A120 3 using the reverse micelle technique. It was hypothesised that changing the crystallite size of the synthesised iron oxide crystallites could lead to the control of the external nanotube diameter. The effect of temperature on the external diameter and productivity was also investigated. It was found through titration and AAS that the iron loading was lower than the expected 15 wt.-%. Furthermore, it was observed that the loading was not consistent through different catalyst samples. This was attributed to incomplete precipitation of iron using the reverse micelle technique, the rigorous cleaning regime implemented and weak metal-support interaction. It was found through XRD and TEM that crystallites in the nanometre range were produced although they were not well distributed over the support. It was also found that the expected linear relationship between water to surfactant ratio and crystallite size was not achieved. Hence the obtained crystallite sizes were significantly different from those obtained in the work by Mabaso.